A Qualitative Evaluation of the Factors Influencing the Adoption of Electronic Payment Systems (SMEs) by SMEs in Nigeria - Igudia, Patrick Ohunmah (European Scientific Journal, ESJ, 2017)
No nation can compete in a global market without developing a versatile and veritable platform for competition especially in trade and commerce through electronic business (e-business) and electronic commerce (e-commerce). Not too long ago, the Nigerian government enacted a visionary policy code-named PSV20:2020 targeted at adopting information and communication technology (ICT) for proper management of the Nigerian economy as part of its effort to become a member of the twenty most economically developed countries in the world by the year 2020. To achieve this, the Nigerian government created the policy of a cashless economy in which all payments for goods and services especially in government businesses have to be done electronically. To make this policy work particularly among the small and medium enterprises (SMEs) in Nigeria, this study examines those factors that influence the adoption and use of electronic payment systems (EPS). A qualitative analytical approach has been adopted in this study. 4 Small and Medium Enterprise owners/managers and 2 officials of two different Banks – the Central Bank of Nigeria (CBN) and United Bank for Africa (UBA) – were interviewed. Data collected from the interview were processed and analysed. Few recommendations were made.